IMPLEMENTASI AKAD WADI’AH YAD DHAMANAH PADA PRODUK SIMPANAN PROGRESIF MENURUT PANDANGAN HUKUM ISLAM (STUDI KASUS DI KOPERASI SERBA USAHA DESA KOTA INDONESIA, KABUPATEN INDRAMAYU) - Nissa Nurhadidah Faried; Rizal Maulana; Ali Aminulloh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to find out the implementation of wadi’ah yad dhamanah contract on product Simpanan Progresif (Progresive Saving) in Koperasi Serba Usaha (KSU) Desa Kota Indonesia, and to find out how Islamic Law view the implementation of the contract. The research method uses qualitative approach, with data collected from observation, interviews, and documentation. The result of the research is that wadi’ah yad dhamanah contract is implemented in Simpanan Progresif KSU Desa Kota Indonesia, consist of an agreement between the depositor and recipient, the utilization of the deposited funds, the bonuses that are not promised, and the saving administration fee. The contract of the transaction is concluded as wadi’ah yad dhamanah muqayyadah. After the research is conducted, Islamic Law views this implementation of wadi’ah yad dhamanah is in accordance with the principles and conditions. Keywords: Wadi’ah yad Dhamanah; Simpanan Progresif; KSU Desa Kota Indonesia